ASSESSMENT OF ROMANIAN ALPINE HABITATS SPATIAL SHIFTS BASED ON CLIMATE CHANGE PREDICTION SCENARIOS - ADRIAN CONSTANTINESCU; JENICĂ HANGANU; ANTHONY LEHMANN; NICOLAS RAY (Revue Roumaine de Géographie)
Shifts in the ecosystems distribution as the result of climate change are of interest for decision-makers in biodiversity conservation at local and European level. This paper presents the use of modeling technique, Maxent (Maximum entropy modeling) and BIOCLIM (environmental envelope model), to estimate the impact of climate change on the Alpine bioregion of Continental Europe for improving the management policy in support of stopping biodiversity loss. The European Union priority habitat 6230 occurring in mountain areas and sub-mountain areas of the Carpathians was selected for modeling being of high priority conservation status in the Natura 2000 network of protected area. Maxent and BIOCLIM were used to create spatial distribution models for Mesophilous oligotrophic mountain pasture and Subalpine oligotrophic pastures. Models were run with 1950–2000 averaged bioclimatic data and double atmospheric CO2 concentration scenario in perspective of the year 2050. In our analyses we have included once all 6320 mapped habitat with Nardus grasslands. Under 1950–2000 climate scenario, both models exhibited high AUC values (> 0.9). The predicted geographical distribution of Mesophilous oligotrophic mountain pasture and Subalpine oligotrophic pastures coded as VNG and PON habitat modeled by Maxent and BIOCLIM shows differences between the modeling approaches, with Maxent predicting smaller areas (12% less) of suitable habitat than BIOCLIM. For the future climate scenario (double CO2) the surface with PON+VNG decreases by 31% for Maxent and 26% for BIOCLIM. However both models show significant shifts of the Nardus habitat due to climate change. The distribution maps obtained indicate vulnerability areas to biodiversity loss and of interest to be monitored. The output of models will contribute to the Black Sea Catchment Observation Systems to be further accessible to scientists, decision-makers and the general public.